Penentuan Batas Dewasa dalam Peralihan Hak Atas Tanah Berdasarkan KUHPerdata dan Surat Edaran Menteri ATR/KA.BPN Nomor 4/SE/I/2015 - Aulia, Khalusha; Trijaya, Mohammad Wendy; Ariani, Nenny Dwi; Kasmawati, Kasmawati; Nurhasanah, Siti (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Law Number 5 of 1960 on Agrarian Principles and its related rules define land rights transfer as transferring ownership or control over land. The transfer of ownership rights raises questions about the minimum age to establish a legal entity. In land services, the age of majority is 18 or after marriage, under Circular Letter of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Head 4/SE/I/2015. In contrast, Article 330 of the Criminal Code defines adulthood at 21 or marriage. These discrepancies in rules create legal confusion for legal organisations who transfer land rights between 18 and 21. The researcher employed a normative legal method to evaluate Indonesian land transfer law and legal certainty among 18–21-year-olds. According to research, a property Deed Official (PPAT) is a public official authorised to issue deeds of transfer of ownership in Indonesia, and all property rights transfers must comply with the UUPA and its laws. In land services, Circular Letter of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (BPN) No. 4/SE/I/2015 is legally binding. When legally mature people transfer land rights according to procedures, their actions are valid and binding. This circular meets the public's land service needs without court orders.